The divine art of dying : living well to life's end - Speerstra, Karen; Anderson, Herbert, 1936- (Fortress Press, 2022)
The Divine Art of Dying aims to empower people who are dying to live as fully as they can until life's end. The book includes reflections from Karen Speerstra's hospice journal and essays written jointly by Speeratra and Herbert Anderson on learning to wait, letting go, giving gifts, and telling stories. Each chapter has suggestions for caregivers.